Appendicectomies in Albanians in Greece: outcomes in a highly mobile immigrant patient population - Ioannidis John PA; Kitsiou Evangelia; Charchanti Antonia; Tatsioni Athina (BMC, 2001)
Abstract Background Albanian immigrants in Greece comprise a highly mobile population with unknown health care profile. We aimed to assess whether these immigrants were more or less likely to undergo laparotomy for suspected appendicitis with negative findings (negative appendicectomy), by performing a controlled study with individual (1:4) matching. We used data from 6 hospitals in the Greek prefecture of Epirus that is bordering Albania. Results Among a total of 2027 non-incidental appendicectomies for suspected appendicitis performed in 1994-1999, 30 patients with Albanian names were matched (for age, sex, time of operation and hospital) to 120 patients with Greek names. The odds for a negative appendicectomy were 3.4-fold higher (95% confidence interval [CI], 1.24-9.31, p = 0.02) in Albanian immigrants than in matched Greek-name subjects. The difference was most prominent in men (odds ratio 20.0, 95% CI, 1.41-285, p = 0.02) while it was not formally significant in women (odds ratio 1.56, 95% CI, 0.44-5.48). The odds for perforation were 1.25-fold higher in Albanian-name immigrants than in Greek-name patients (95% CI 0.44- 3.57). Conclusions Albanian immigrants in Greece are at high risk for negative appendicectomies. Socioeconomic, cultural and language parameters underlying health care inequalities in highly mobile immigrant populations need better study.